Using 5E Learning Cycle-Based Laboratory Activity in Improving Students’ Problem Solving Skills on Mixture Separation Topic - Fadiawati, Noor; Diawati, Chansyanah; Meidayanti, Reni; Syamsuri, M. Mahfudz Fauzi (Jurnal Pendidikan Progresif, 2019)
Using 5E learning cycle-based laboratory activity in improving students’ problem solving skills on mixture separation topic. Objectives: The aim of this study was to describe the effectivity of laboratory activity on mixture separation topic based on 5E learning cycle to improve students’ problem solving skills. Methods: This quasi-experimental study was carried out in the SMPN 33 Bandar Lampung by using the matching only pretest-posttest control group design. The 7th-D and the 7th-E grade were used as experimental and control classes, respectively, which they were obtained by using purposive sampling technique. Findings: The effectivity of 5E learning cycle-based laboratory activity measured based on the n-gainand the effect size values. The n-gain value of experimental and control classes were in medium (0.52) and low (0.29) categorized, respectively. The effect size value was in large categorized (0.67). Conclusion: These results indicated that 5E learning cycle-based laboratory activity could be effective to improve students’ problem solving skills to separate of mixture. Keywords: problem solving skills, laboratory activity, 5E learning cycle. DOI: http://dx.doi.org/10.23960/jpp.v9.i2.201922